Analgesic Action of Catechin on Chronic Constriction Injury–Induced Neuropathic Pain in Sprague–Dawley Rats - Foudah, Ahmed I.; Alqarni, Mohammed H.; Devi, Sushma; Singh, Akanksha; Alam, Aftab; Alam, Pravej; Singh, Sima (Frontiers in Pharmacology, 2022)
Chronic neuropathy is a common and debilitating problem and poses a significant challenge to health care worldwide. Natural compounds have received considerable attention as potential sources of new drugs for the treatment of neuropsychiatric pain. Catechin is a well-known novel flavonoid with several therapeutic properties, notably in neurodegenerative diseases. The current study is designed to investigate the role of catechin in neuroprotective activity in the chronic constriction injury (CCI) model. Apparently healthy adult male Sprague-Dawley rats weighing 160-190 g (8 weeks old) were selected and grouped into the following: Sham (distilled water), CCI group (CCI), standard (CCI + Pregabalin (10 mg/kg, p.o.), test catechin (CCI + catechin (50 µg/kg p.o) and test catechin (CCI + catechin (100 µg/kg p.o) for 28 days. Behavioral, thermal, and mechanical changes were evaluated. The results showed that mechanical allodynia and thermal hyperalgesia were reduced in the catechin-treated group compared to the CCI group. In addition, the relationship between the analgesic effect of catechin and the expression of TNF-α, IL-6, and IL-β were established. The results showed that catechin reversed the signs of neuropathic pain. It also decreased the levels of TNF-α, IL-6, and IL-β in the rat brain. Therefore, the results suggested that catechin has promising potential in the treatment and management of neuropathic pain by decreasing the levels of NF-κβ regulated inflammatory cytokines in the chronic constriction injury model.